Phylogenomics Places Orphan Protistan Lineages in a Novel Eukaryotic Super-Group. (19th January 2018) - Brown, Matthew W; Heiss, Aaron A; Kamikawa, Ryoma; Inagaki, Yuji; Yabuki, Akinori; Tice, Alexander K; Shiratori, Takashi; Ishida, Ken-Ichiro; Hashimoto, Tetsuo; Simpson, Alastair G B; Roger, Andrew J
Abstract: Recent phylogenetic analyses position certain "orphan" protist lineages deep in the tree of eukaryotic life, but their exact placements are poorly resolved. We conducted phylogenomic analyses that incorporate deeply sequenced transcriptomes from representatives of collodictyonids (diphylleids), rigifilids, Mantamonas, and ancyromonads (planomonads). Analyses of 351 genes, using site-heterogeneous mixture models, strongly support a novel super-group-level clade that includes collodictyonids, rigifilids, and Mantamonas, which we name "CRuMs". Further, they robustly place CRuMs as the closest branch to Amorphea (including animals and fungi). Ancyromonads are strongly inferred to be more distantly related to Amorphea than are CRuMs. They emerge either as sister to malawimonads, or as a separate deeper branch. CRuMs and ancyromonads represent two distinct major groups that branch deeply on the lineage that includes animals, near the most commonly inferred root of the eukaryote tree. This makes both groups crucial in examinations of the deepest-level history of extant eukaryotes.